Unlocking the potential of health systems using privacy preserving record linkage: A pilot project exploring the research potential of developing a linkable general practice dataset. (8th November 2019) - Boyd, James; Lee, Yuen Ai; Brown, Adrian; Randall, Sean; Ferrante, Anna
No abstract available